Growth, Development, and Seed Biology of Feather Fingergrass (Chloris virgata) in Southern Australia. Issue 3 (6th February 2017) - Ngo, The D.; Boutsalis, Peter; Preston, Christopher; Gill, Gurjeet
Abstract : Feather fingergrass is a major weed in agricultural systems in northern Australia and has now spread to southern Australia. To better understand the biology of this emerging weed species, its growth, development, and seed biology were examined. Under field conditions in South Australia, seedlings that emerged after summer rainfall events required 1, 200 growing degree days from emergence to mature seed production and produced 700 g m −2 shoot biomass. Plants produced up to 1, 000 seeds panicle −1 and more than 40, 000 seeds plant −1, with seed weight ranging from 0.36 to 0.46 mg. Harvested seeds were dormant for a period of about 2 mo and required 5 mo of after-ripening to reach 50% germination. Freshly harvested seed could be released from dormancy by pretreatment with 564 mM sodium hypochlorite for 30 min. Light significantly increased germination. Seed could germinate over a wide temperature range (10 to 40 C), with maximum germination at 15 to 25 C. At 20 to 25 C, 50% germination was reached within 2.7 to 3.3 d, and the predicted base temperature to germinate was 2.1 to 3.0 C. The osmotic potential and NaCl concentration required to inhibit germination by 50% were −0.16 to −0.20 MPa and 90 to 124 mM, respectively. Seedling emergence was highest (76%) for seeds present on soil surface and was significantly reduced by burial at 1 (57%), 2 (49%), and 5 cm (9%). Under field conditions, seeds buried in the soil persisted longer than those left on the soil surface, and low spring–summer rainfall increased seed persistence. This study provides important information on growth, development, and seed biology of feather fingergrass that will contribute to the development of a more effective management program for this weed species in Australia.